O tempo como condutor da narrativa: tempo e focalização em A chegada (2016) - Tavares, Francisco Danillo Pereira (2021)
The elements which compose a narrative are fundamental in the logical organization of the story to be narrated. Currently, narratological studies work with many supports used to tell stories, including words, images, sounds, etc. Cinema is a medium which brings together different signs in the construction of its meanings. In general, narratives manipulate the time of the story to fit within the time of the discourse, in addition to a perspective assumed in the narration of the story. In Arrival, a 2016 film directed by Denis Villeneuve and adapted from Story of Your Life, a short story by Ted Chiang, time is structurally manipulated through the perception and point of view of the protagonist Louise Banks during her contact with alien. Articulating time as a narrative category by Gérard Genette (2017) and the cinematographic specificities proposed by André Gaudreault and François Jost (2009). The research is based in terms of narrative focus and focusing on authors as Gérard Genette (2017), Jean Pouillon (1974) and Norman Friedman (1967). Also, the film belongs to the science fiction genre, it is essential observe how the film works with themes such as otherness and the relationship between the self to the others. A recurrent theme in the science fiction. Therefore, the theoretical contribution to science fiction is based on Fátima Régis (2006) and Adam Roberts (2018). Finally, the study analyzes how the filmic narrative constitutes the perspective through a non-linear narrative time, and how it chooses what it hides and what it reveals to viewer by the point of view assumed.